Peranaan Guru PAK dalam Mengatasi Stres Siswa (Studi SMA Negeri 12 Ambon) - Adolfina Putnarubun (SOSCIED, 2021)
Stress is an unavoidable reality of everyday life. The stress experienced by students at a mild level actually makes students excited to learn, but at a later stage stress can cause complaints from students such as often feeling sleepy at school because every day they have to go home at night and after that they have to do the assignments of the teachers. more and more day by day. This can consume all of the student's workforce, causing fatigue and tiredness. When this happens, the overload can cause stress, in the form of physical and mental fatigue, decreased endurance, and emotional instability. From the results of research conducted by the author at SMA 12 Negeri Ambon, it shows that excessive stress experienced by some students has a negative impact on students themselves, with the inability to carry out school activities and fear of failure to achieve achievement. Other manifestations of stress among students include alcohol use, drug abuse, suicide and premature pregnancy. Understanding this problem, the role of PAK teachers is very much needed in shaping the personality of the students themselves, for that PAK teachers play an important role in the mentoring process for every student who has problems, so that students can be guided to manage their stress so as not to have a negative impact on the student or the people around him.